Enhancing Elementary Students’ Interest and Learning Outcomes in Social Studies Through the Poster Session Strategy Assisted by Audio-Visual Media - Suardi, Suardi; Nurhasanah , Nurhasanah; Arifin, Jamaluddin (Journal of Educational Sciences, 2025)
This study explores the effect of the Poster Session learning strategy, supported by audio-visual media, on students’ interest and learning outcomes in social studies among fourth-grade elementary students in Gugus V, Lau District, Maros Regency, Indonesia. A quasi-experimental design with a nonequivalent control group was utilized, involving 40 students equally divided into experimental and control groups. The experimental group received instruction using the Poster Session strategy, while the control group followed conventional methods. Data were collected through pretest and posttest questionnaires measuring learning interest and achievement. The results showed a notable improvement in the experimental group. Learning interest rose from a mean of 67.20 to 88.40, compared to the control group’s increase from 61.75 to 74.40. Similarly, academic performance in the experimental group improved from 62.20 to 84.00, while the control group showed only a modest gain from 55.30 to 63.10. MANOVA analysis confirmed the significance of the intervention on both outcomes (Pillai’s Trace = 0.775, p < 0.001). These findings indicate that integrating the Poster Session strategy with audio-visual aids enhances student engagement and academic achievement. The study recommends broader implementation of this approach in elementary education to support deeper learning and sustained interest in social studies.